Pathogenicity and virulence of Erysipelothrix Rhusiopathiae isolatives - Пінчук, Н. Г. (Scientific Progress & Innovations, 2018)
Erysipelothrix rhusiopathiae is heterogeneous in the ability to form toxins, enzymes and other pathogenicity factors. Despite the fact that the pathogens of pigs’ erysipelas belong to the number of microorganisms that are easy to isolate and identify, without using complex diagnostic tools and techniques, the issue of the pathogenicity of Erysipelothrix rhusiopathiae and the presence of pathogenic factors involved in the mechanisms of the onset and development of pathological processes remains. The material for the study was 47 isolates of Erysipelothrix rhusiopathiae, isolated from pigs with a septic form of the disease, in chronic and atypical course of the disease, and from clinically healthy pigs; 2 isolates are isolated from poultry (laying hens); 3 – from turkeys; 2 – pigeons. In this article we have studied and characterized 54 field Erysipelothrix rhusiopathiae isolates isolated from different regions of Ukraine from different species of animals and found that 52 % of isolates belong to medium virulent; the smallest percentage (13 %) is highly virulent and 35 %, respectively, weakly virulent isolates. As a result of the studies, it was found that 7 isolates belonging to the group of highly virulent cultures Erysipelothrix rhusiopathiae (6 isolated from pathological material of dead pigs and 1 – from turkeys; Log LD50 was 1.7–2.2). A slightly lower virulence was found in 24 cultures of Erysipelothrix rhusiopathiae isolated from the pathological material of dead pigs and 2 from turkeys, 1 from chickens, 1 – from the pigeon; Log LD50 was 2.93–4.05. 17 isolates of Erysipelothrix rhusiopathiae isolated from pigs, 1 from laying hens and 1 from the pigeon were classified as weakly virulent (Log LD50> 6.0). It should be noted that highly virulent isolates were isolated from the dead pigs of the South-East region of Ukraine (Autonomous Republic of Crimea from Sevastopol, Dnipropetrovsk, Zaporizhzhia, Kirovograd, Mykolayiv, Odesa and Kherson regions). The obtained results of the research became the basis for selection of 7 highly virulent isolates of Erysipelothrix rhusiopathiae, which can be used as controls for controlling the quality of vaccines live and inactivated against white skinned pigs in laboratory white mice.